2020
DOI: 10.4236/jss.2020.82015
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Efficiency Structure Analysis Model of Shipbuilding Based on Driving Factors: The Case of Chinese Shipyard

Abstract: The purpose of this paper is to build an efficiency evaluation model based on efficiency drivers. Building technique, resource ability and management level are the three main driving factors in production efficiency of shipbuilding. Two-stage internal production efficiency structure analysis model (ESAM) firstly decomposes the shipbuilding system efficiency into three dimensions of subsystem efficiency structures to express the driving effect of the three driving factors of technique, operation and management.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The problem of complex products in the "main manufacturer-supplier" model has been studied by many scholars, focusing on two aspects: First, the research is carried out from the perspective of contract design based on game theory. Based on the evolutionary game, Xue et al [ 17 , 18 ] proposed a dynamic penalty mechanism that is more conducive to complex product quality control from the perspective of contract design, and designed a contractual game model of quality improvement incentive gain-sharing contracts between the main manufacturers and suppliers of large ships, taking into account supply chain synergy factors. Liu and Wu [ 19 ] designed a class of quality incentive contracts for complex product supply chains by considering the effects of short-term economic benefits and long-term quality reputation, and by constructing a "benefit-reputation" utility function for quality cooperators in the supply chain to achieve a win-win situation in terms of their overall utility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem of complex products in the "main manufacturer-supplier" model has been studied by many scholars, focusing on two aspects: First, the research is carried out from the perspective of contract design based on game theory. Based on the evolutionary game, Xue et al [ 17 , 18 ] proposed a dynamic penalty mechanism that is more conducive to complex product quality control from the perspective of contract design, and designed a contractual game model of quality improvement incentive gain-sharing contracts between the main manufacturers and suppliers of large ships, taking into account supply chain synergy factors. Liu and Wu [ 19 ] designed a class of quality incentive contracts for complex product supply chains by considering the effects of short-term economic benefits and long-term quality reputation, and by constructing a "benefit-reputation" utility function for quality cooperators in the supply chain to achieve a win-win situation in terms of their overall utility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li, Zhang, and Liu (2017) [6] used stochastic frontier analysis to calculate the technical efficiency of the shipbuilding industry, and then further analyzed the regional development differences as well as the influencing factors of technical efficiency. Xue et al (2020) [20] constructed a two-stage internal production efficiency structure analysis model (ESAM) to analyze the efficiency of the internal operation, process, and management of Chinese shipyards.…”
Section: The Marine Ship Industry Chainmentioning
confidence: 99%
“…They observed that rules based on combinations of the time criticality index, resource criticality index and shortest processing time yield the most and the least efficient trade-off, respectively, between time and resource-oriented objectives. Xue et al (2020) indicated that building technique, resource ability and management level are the three major drivers of the production efficiency of shipbuilding. Based on an empirical study on one of the largest state-owned shipbuilding companies in China, they suggested that improving management Productivity of major shipyards efficiency and technique efficiency should be the main direction taken to improve Chinese shipbuilding efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%